2014
DOI: 10.1007/s11064-014-1331-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol Promotes Augmented Dopamine Release in the Lesioned Striatum of 6-Hydroxydopamine Treated Rats

Abstract: Current therapies for Parkinson's disease (PD) offer symptomatic relief but do not provide a cure or slow the disease process. Treatments that could halt progression of the disease or help restore function to damaged neurons would be of substantial benefit. Calcitriol, the active metabolite of vitamin D, has been shown to have significant effects on the brain. These effects include upregulating trophic factor levels, and reducing the severity of some central nervous system lesions. While previous studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Progression of PD symptoms is associated with the degeneration of dopaminergic neurons. As previously outlined, preclinical studies in neurotoxicity animal models of this disease confirm that 1,25(OH) 2 D 3 can restore dopamine levels in striatum and ameliorate dopamine neuron death induced by intra-cerebral administration of 6-OHDA (Wang et al, 2001;Smith et al, 2006;Sanchez et al, 2009;Cass et al, 2012Cass et al, , 2014. Cass et al and Sanchez et al have showed that vitamin D increases GDNF in the lesioned striatum indicating this trophic agent may be the mediating factor for vitamin D's neuroprotective actions on dopamine neurons.…”
Section: 25(oh) 2 D 3 Directly Modulates Th Expression In Neuronal mentioning
confidence: 72%
See 3 more Smart Citations
“…Progression of PD symptoms is associated with the degeneration of dopaminergic neurons. As previously outlined, preclinical studies in neurotoxicity animal models of this disease confirm that 1,25(OH) 2 D 3 can restore dopamine levels in striatum and ameliorate dopamine neuron death induced by intra-cerebral administration of 6-OHDA (Wang et al, 2001;Smith et al, 2006;Sanchez et al, 2009;Cass et al, 2012Cass et al, , 2014. Cass et al and Sanchez et al have showed that vitamin D increases GDNF in the lesioned striatum indicating this trophic agent may be the mediating factor for vitamin D's neuroprotective actions on dopamine neurons.…”
Section: 25(oh) 2 D 3 Directly Modulates Th Expression In Neuronal mentioning
confidence: 72%
“…A number of studies have shown that 1,25(OH) 2 D 3 can act as a neuroprotective agent for dopaminergic neurons (Wang et al, 2001;Cass et al, 2006;Smith et al, 2006;Sanchez et al, 2009;Cass et al, 2012Cass et al, , 2014. These data and the epidemiological findings linking low levels of vitamin D with increased risk of Parkinson's disease (PD) (Newmark and Newmark, 2007;Evatt et al, 2008Evatt et al, , 2011Knekt et al, 2010;Peterson et al, 2013) have led to a clinical trials of vitamin D in this disease.…”
Section: 25(oh) 2 D 3 Directly Modulates Th Expression In Neuronal mentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism by which VD3 promotes recovery of dopaminergic release and content remains to be determined, but evidences indicated its potential for affecting calcium metabolism, apoptosis, inflammation, immunomodulation, detoxification, and upregulation of neurotrophins [5153]. …”
Section: Discussionmentioning
confidence: 99%